Sixth Art Circuit : De Slang. - de Vlam, Ludovic; Vanbelleghem, Kurt (Bruges : De Slang Office, 2002)
Bernolet, Ignace ; Callewaert, Marie-Jeanne ; Clarysse, Johan ; Daled, Jeroen ; De Vliegher, Jan ; Eneman, Hans ; Goetinck, Pierre ; Jonckheere, Peter ; Molleman, Linda ; Schotte, Monique ; Verhaeghe, Jan ; Verhaeghe, Ria ; Vynck, Willy
The Sixth Art Circuit of De Slang is part of Octopus, May 18th - May 20th, May 25th - May 26th, Juni 1st - June 2nd, 2002
boek